Worldwide distribution of genotypes in Acanthamoeba keratitis : a systematic review - Diehl, Maria Luísa Nunes (2020)
Acanthamoeba spp. are among the most prevalent protozoa distributed in the world, causing diseases as Acanthamoeba keratitis, which is a painful and severe sight threatening corneal disease that in some cases can cause even blindness. In recent years, the prevalence of Acanthamoeba keratitis has rapidly increased, making it increasingly recognized as important for human health. This systematic review proposes to analyze the frequency of genotypes of the genus Acanthamoeba in keratitis cases around the world, as well as to analyze the types of samples collected and the identification methods used. Most cases were found in Asia and Europe. Undoubtedly, the T4 genotype was the most prevalent worldwide, followed by T3, T15, T11 and T5. Besides that, T4 genotype was also related to a greater number of species of Acanthamoeba . Given the differences in pathogenicity, virulence, 1 susceptibility to treatment and clinical outcomes between genotypes, genotyping of all isolates from cases of Acanthamoeba keratitis is essential to have a better correlation between in vitro and in vivo efficacy, resulting in better drug therapies and successful treatment in cases of this important ocular infection.